Assessment of the primary productivity of phytoplankton in Lake Sebu - Cordero, Mary Ann W. (NDMU Research Journal: official research journal of Notre Dame of Marbel University, 1996)
Lakes are a home for aquatic animals which form an important part of the food chain. In assessing the primary productivity of phytoplankton in Lake Sebu, the study considers both the physical and chemical properties of the water. The productivity of the phytoplankton was measured by direct cell count using haemacytometer, by chlorophyll analysis and by dry weight determination. This analysis forms a substantial basis in evaluating the productivity in Lake Sebu.